Lexicographic Treatment of Zero Equivalence in isiZulu Dictionaries - Prinsloo, D.J.; Zondi, Nompumelelo (Lexikos, 2020)
One of the main tasks of compilers of bilingual dictionaries is to find suitable translation equivalents for source language lemmas in the target language. It could be expected that to a large degree one should find full equivalence, or at least partial equivalents in the target language and that there might not be many instances where such translation equivalents are not available. Typically common words such as table, chair, man, woman come to mind and they are most likely to have equivalents in the target language. This article focuses on lexical and referential gaps between English and isiZulu, and their treatment in English and isiZulu paper dictionaries. The aim is to determine to what extent suitable translation equivalents are available for English and isiZulu lemmas and what the nature, extent and treatment strategies are in cases where such equivalents are not available. It will be shown that the extent of zero equivalence is much higher for this language pair than expected in general literature on zero equivalents. In some cases a specific concept is known in the target language but the target language has no word for it but in many instances the concept itself is unknown in the target language which implies that the language will also not have a word for such a concept.